New Formulation of Paraquat: A Step Forward but in the Wrong Direction? - Bateman, D. Nicholas (PLoS medicine, 2008)
There was some internal inconsistency in the approaches used to alter the formulation, in that gastric emptying was intended to be delayed by the use of an alginate that would gel in gastric acid.\n Quantities of paraquat ingested in this study were very substantial, and the overall approach of this new formulation would only be effective if a very high proportion of patients are very close to the borderline between a lethal and non-lethal dose--much lower than the median doses ingested by patients in this study. In the more affluent countries of the world, toxicity prevention by product ban may be achievable, but seems less readily acceptable in the economic margins of subsistence farming.